2011
DOI: 10.1007/s00392-011-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the temporal release pattern of copeptin with conventional biomarkers in acute myocardial infarction

Abstract: BackgroundEarly detection of acute myocardial infarction (AMI) using cardiac biomarkers of myocardial necrosis remains limited since these biomarkers do not rise within the first hours from onset of AMI. We aimed to compare the temporal release pattern of the C-terminal portion of provasopressin (copeptin) with conventional cardiac biomarkers, including creatine kinase isoenzyme (CK-MB), cardiac troponin T (cTnT), and high-sensitivity cTnT (hs-cTnT), in patients with ST-elevation AMI.MethodsWe included 145 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 31 publications
2
57
0
2
Order By: Relevance
“…42 The association of hs-cTnT with copeptin in a common biomarker panel slightly increased the rate of ACS detection at admission. 43 A more recent study of copeptin on 195 patients with a 5-year follow-up demonstrated that copectin is an independent long-term prognostic indicator in HfrEF patients.…”
Section: Copeptinmentioning
confidence: 99%
“…42 The association of hs-cTnT with copeptin in a common biomarker panel slightly increased the rate of ACS detection at admission. 43 A more recent study of copeptin on 195 patients with a 5-year follow-up demonstrated that copectin is an independent long-term prognostic indicator in HfrEF patients.…”
Section: Copeptinmentioning
confidence: 99%
“…The most direct application for copeptin measurement is in the diagnosis of central diabetes insipidus, a disease caused by a primary vasopressin synthesis defect [4]. Measurement of copeptin has also been suggested in the early exclusion of acute myocardial infarction among patients with suspected acute coronary syndrome [5,6,10]. In addition, copeptin measurement provides prognostic information in several acute conditions such as myocardial infarction [11], heart failure [12][13][14][15][16], infection [17][18][19], stroke [20,21], traumatic…”
Section: Introductionmentioning
confidence: 99%
“…Так, в исследовании Gu YL, et al (2011) [15] у 145 больных ИМ с подъемом сегмента ST на ЭКГ определяли в динамике уровни в крови копептина, КК-МВ и Tn Т. Обнаружено, что пик содержания копептина регистрировался немедленно после развития симптомов ИМ и составлял 249 пмоль/л. Пиковые значения КК-МВ и Tn Т регистри-ровались гораздо позже и составляли 275 ед./л и 5,75 мкг/л, соответственно.…”
unclassified
“…Механизм повышения копептина в крови при ИМ, по мнению Gu YL, et al (2011) [15], обусловлен снижением сердечного выброса, изменениями гемо-динамики и/или АД. Самостоятельное значение Аналогичные данные получены в крупном много-центровом исследовании COPED-MIRRO (2014) [21].…”
unclassified